Early prognostic value of multimodal neurophysiological monitoring in asphyxiated infants undergoing hypothermia. Issue 1 (January 2019) - Lori, S.; Krakowska-Kubiszewska, A.; Bastianelli, M.; Gabbanini, S.; Cossu, C.; Bertini, G.; Lolli, F.
Abstract : The prognostic correlation between the early lack of cortical and the development of cerebral palsy/neurodevelopmental impairment is reported. 1, 2 . We utilized the "standardized 1-h multimodal neurophysiological monitoring" (1-hMNM: simultaneous VEEG-PES-continuous recording 3 ) in asphyxiated neonates undergoing hypothermia, to determine the early predictive prognostic value of VEEG and PES, individually and together (1-hMNM). The "Bayley for Infant and Toddler Development" Scales (BSID-III, 12–24 months) was used for neurological outcome. We evaluated, retrospectively, 28 term-neonates (mean GA 39 + 1, 13 F) with hypoxic brain damage studied with1-hMNM in the first weeks of life; the MRI and Ultrasound was also performed. 14 neonates completed the follow-up at 24 months (5 dead). We used the STATA statistical software (version 14). The specificity value of the PES was 50% (90% CI 15.3–84.7) and of the VEEG = 16.7 (90% CI 0.851–58.2). The sensitivity of VEEG + PES-continuous (1 h-MNM) was to 87.5% (90% CI 52.9–99.4) and specificity 66.7% (90% CI 27.1–93.7) with PPV of 89% (90% CI 34.3 −99) and NPV equal to 77.8% (90% CI 45–95.9). The use of 1 h-MNM at an early stage increases the predictability of neurological impairment by not increasing costs and discomfort for the newborn.